Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPA dengan Pendekatan Inkuiri di Kelas IV SD Negeri 21 Lubuk Alung Kabupaten Padang Pariaman - DEWITA, FITRA; MAIMUNAH, MAIMUNAH; MUHAMMADI, MUHAMMADI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
The purpose of research is to describe Increasing student learning outcomes in science learning by inquiry approach in the fourth grade SDN 21 Lubuk Alung Padang Pariaman district. This research is a class act. The results obtained in the first cycle of planning 78.6% 92.9% B to be qualified with qualification SB cycled II. On the implementation of aspects of the first cycle teachers qualified B increased 77.1% to 91.7% qualified SB in the second cycle. On the implementation of aspects of the students in the first cycle of qualified B increased 72.9% to 93.8% qualified SB. In the second cycle, increasing student learning in the cognitive aspects of 71.50 in the first cycle to 85.75 in the second cycle. On the affective aspects of 73.98 in the first cycle to 88.8 in the second cycle. And the psychomotor aspects of 73, 8 on silkus I to 85.85 in the second cycle. Based on these results it can be concluded that learning science using inquiry approach to improve student learning outcomes in primary schools.